Rectus abdominis muscle activation during abdominal crunches in volleyball and hockey player - Mohd. Hashim, Asha Hasnimy; Abdul Rahman, Mohd. Shafie; Ibrahim, Halijah; Zainuddin, Zainal Abidin (2007)

(untitled)
Abdominal crunches has widely known as one method of exercise for strengthen abdominal muscle especially rectus abdominis. However, not all muscle requires abdominal crunches to strengthen this muscle. This is due to the nature of sports that requires specific of exercise to strengthen rectus abdominis. The aim of this research is to identify and analyse the rectus abdominis muscle activation while performing abdominal crunches between volleyball and hockey player. Subjects were chosen from university volleyball and hockey team and in the range of ideal body weight based on the Body Mass Index (BMI) that been measured. The data was collected by using Biopac Student Lab: (Electromyography) and was analysed using Statistical Packages for Social Science version 14.0 (SPSS 14.0). The results indicate that there are differences in rectus abdominis muscle activity between volleyball and hockey player while performing abdominal crunches. It also shows that the muscle activation within rectus abdominis sub-unit are varies between volleyball and hockey players.